Rhinitis medicamentosa: mechanism, treatment options and methods of prevention - Byrska, Martyna; Barska-Kobylińska, Hanna; Janura, Marta; Weimann , Maja; Przywara, Grzegorz; Biegańska, Oliwia; Biczak, Emilia; Malaka , Ewa Katarzyna; Zubiak, Marlena; Langner, Sara (Journal of Education, Health and Sport, 2025)
Introduction: Rhinitis medicamentosa (RM) is a chronic inflammatory condition of the nasal mucosa caused by excessive use of topical nasal decongestants. This leads to tachyphylaxis, increased vascular permeability, chronic inflammation, and structural changes in the nasal mucosa, resulting in medication dependence and persistent nasal congestion. Study Objective: This study aims to discuss the mechanisms underlying RM, its clinical consequences, diagnostic methods, and therapeutic strategies. Additionally, it highlights the importance of patient education and healthcare professional awareness in preventing RM and reducing its prevalence. Materials and Methods: A comprehensive literature review was conducted, analysing current scientific research on RM, including its pathophysiology, diagnostics and treatment methods. Additionally, the review explored the systemic implications, association with addiction, and the importance of prevention and education in managing the condition. Conclusions: There is a need for better education for both patients and healthcare professionals regarding RM. A key element of RM prevention is informing patients about the importance of limiting the use of these medications to a maximum of 5–7 days. Furthermore, further research is necessary to develop more effective therapeutic methods, including the potential use of alternative substances such as xylitol or hyaluronic acid in the regeneration of the nasal mucosa.